Analisis Hubungan Dagang Indonesia-Jepang Pada Komoditas Tekstil di Bawah Kerja Sama APEC - Hidayah, Lailatul; Daspar, Daspar (Innovative: Journal Of Social Science Research, 2025)
Indonesia's textile industry has significant potential for export to the Japanese market, but the utilization of trade cooperation facilitated by APEC is still not optimal. While APEC offers open and barrier-free trade policies, textile industry players in Indonesia are still limited in utilizing these facilities. Several factors hinder this, including a lack of understanding of APEC’s technical policies and the growing competition from countries like Vietnam, China, and Bangladesh. These countries are more aggressive in marketing their textile products to Japan, supported by production efficiency, advanced technology, and stronger bilateral trade partnerships. Moreover, Japan’s market is very selective about the quality and ever-changing fashion trends, making it difficult for many Indonesian industry players to meet the required standards. Non-tariff barriers such as technical certifications, environmental regulations, and product safety standards also pose challenges, especially for SMEs trying to penetrate the Japanese market. Promotion and branding of Indonesian textile products in Japan are still very limited, leading to low recognition of Indonesian products. Therefore, closer synergy between the government and the industry is needed, focusing on enhancing production capacity, product quality, and more intensive promotion. The government must also strengthen economic diplomacy and facilitate research and training collaborations to improve competitiveness. Although APEC is not a regulator, it can serve as a facilitator to encourage more productive cooperation.